Technological lever as a tool for product-engineering enterprise technology platforms - Косенко, Олександра Петрівна (Technology audit and production reserves, 2015)
The article is devoted to innovative methods for assessing the commercial potential of intellectual property. It is proved that an important indicator of market opportunities intelligently estimation method patents are weighted citation. With its use of available light practical value of patents based on the frequency of citations in other patents. As an evaluation criterion suggested to use leverage technology that plays as the ability to distribute innovative enterprise advanced knowledge, technology, application know-how gained in the process of establishing a base of intellectual technologies in a variety of products to end users. Methodical approaches identifying business opportunities intelligent technology for the developer and for its customers. The concept of leverage effect technology allows significantly increase the efficiency of the process by creating product product-technology platforms as a developer and a potential consumer technology innovations.